Professional Ethics and Notary Responsibilities Review of Law Number 2 of 2014 and the Notary Code of Ethics of 2015 - Muh Tabran; marilang; Hamsir; Firda, A. (Indonesian Journal of Entrepreneurship and Startups, 2023)
Notary professional positions that provide a form of service to the community, notaries need to determine moral standards in carrying out duties, and authority and obligations. the importance of the role and position of a notary in society, the notary is obliged to uphold the morals, dignity and honor of public officials. Professional ethics and moral responsibility of a notary is the basis for the implementation of notary professional ethics and is governed by notary profession law. In essence, a notary is a general legal official who is authorized to act honestly in all actions, agreements and statutory regulations. Personnel who occupy the position of notary public must comply with the Law on Notary Practices and the Code of Professional Ethics. When carrying out duties and serving social interests, a person must maintain his dignity and may not take illegal actions against the provisions in carrying out the duties of a notary